Correlation between social intelligence and motor development of children in the 4.0 era - Wijaya, Ridho Gata; Ubaedi, Ubaedi; Ndayizeye, Oscar; Antoni, Muhammad Sigit; Sotomi, Emanuel (Universitas Negeri Yogyakarta, 2024)
Social intelligence and motor skills are essential for a child's development. This study in the Sleman Regency investigates the relationship between social intelligence and motor skills development in 170 primary school students. The data collection instruments included a Social Skills Rating Scale (SSRS-T), a questionnaire, and Nurhasan's motor ability test. The data used meet the normality and linearity conditions, as indicated by the coefficients of 0.721 and 0.108, each greater than 0.05, respectively. The results show that 71.17% of the sampled students have above-average social intelligence (SI). The sampled children's SI can be grouped into very good (top 10%), good (next 18.82%), average (middle 42.35%), poor (next 25.29%), and extremely poor (bottom 25.29%); the respondents' rates in each category are as mentioned. Regarding motor development, 8.24% of the students were categorised as very good, 20.59% as good, 36.47% as average, 32.35% as poor, and 2.35% as extremely poor. The study found a moderate positive correlation (r value of 0.344) between social intelligence and motor development. With the determinant R2=0.118, given the variable indicators, high importance on communication and physical interaction explains at least 11.8% of the variation in the students' motor skills development. The researchers recommend that further studies on the habits of electronic gadget usage by the sampled children be carried out to shed light on unexploited frontiers for children with poor and extremely poor social intelligence.